Analysis of Consumer Motivation for Using Cryptocurrency in Indonesia - Hatta Muttaqin; Rama Deswantiyar; Rano Kartono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Currently, the use of cryptocurrency has been increasingly popular around the globe. In fact, cryptocurrency became the special topic in the 2018 G20 Summit in Buenos Aires. Moreover, in 2021 El Salvador has become the first country in the world to declare Bitcoin as its legal medium of exchange other than US Dollar. In Indonesia the use of cryptocurrency is also growing rapidly. According to Indonesia Crypto Outlook Report 2020, there was a 2,263% increase of cryptocurrencies users from 2015 to 2020, with the total number of users in Indonesia reaching 1,547,329 persons. Based on this development, it is necessary to conduct research to observe what factors influence the use of cryptocurrency in Indonesia. Previous study about behavioral intention in the use of cryptocurrency found four influencing factors, which are performance expectancy, social influence, effort expectancy and facilitating conditions. This research aims to determine the influence of those four factors to behavioral intention to use cryptocurrency in Indonesia. It uses a quantitative approach with survey as its method. Furthermore, the data is analyzed using multiple linear regression techniques. Tests carried out included validity & reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, F tests and t tests. The results of the study show that performance expectancy, social influence, effort expectancy and facilitating conditions have a significant effect on behavioral intention to use cryptocurrency.